Web-Based Mind Mapping Learning Media to Improve Students' Conceptual Understanding of Magnetic Field Material at SMAN Kota Bengkulu - Refiana, Refiana; Risdianto, Eko; Purwanto, Andik (CV Media Inti Teknologi, 2024)
This study aims to describe the feasibility and perception of web- based mind mapping learning media to improve students' conceptual understanding of magnetic field material from students. This study is a research and development (R&D) with a 3D model with steps of definition, design, and development. The data collection technique is a non-test technique that uses observation data, document review, and questionnaires. The data analysis techniques used are descriptive, qualitative, and quantitative methods. The subjects used in this study were physics teachers and grade XII students at SMA 9 Bengkulu City. The results of the study obtained data that the mind mapping learning media developed is included in the very feasible criteria with an average percentage of 86%, so it is worthy of being tested for readability so that it gets a very good perception assessment with an average percentage of 87%. Based on the results of the study obtained, it can be concluded that the mind mapping learning media developed received a very good response and can be used as an alternative learning media in the classroom.